2019
DOI: 10.1021/jacs.9b06956
|View full text |Cite
|
Sign up to set email alerts
|

Unified Approach to the Chemoselective α-Functionalization of Amides with Heteroatom Nucleophiles

Abstract: Functionalization at the α-position of carbonyl compounds has classically relied on enolate chemistry. As a result, the generation of a new C–X bond, where X is more electronegative than carbon requires an oxidation event. Herein we show that, by rendering the α-position of amides electrophilic through a mild and chemoselective umpolung transformation, a broad range of widely available oxygen, nitrogen, sulfur, and halogen nucleophiles can be used to generate α-functionalized amides. More than 60 examples are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 29 publications
(53 reference statements)
0
45
0
6
Order By: Relevance
“…Furthermore, we were pleased to find that 2‐norbornyl amides undergo oxidative cyclopropanation through amide umpolung chemistry using 2‐iodo pyridine, trifluoromethanesulfonic anhydride, and pyridine‐ N ‐oxide (PNO) subsequently . Even though a pyridine base is used for this approach, elimination towards the norbornene derivative 36 represents only a minor reaction pathway (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we were pleased to find that 2‐norbornyl amides undergo oxidative cyclopropanation through amide umpolung chemistry using 2‐iodo pyridine, trifluoromethanesulfonic anhydride, and pyridine‐ N ‐oxide (PNO) subsequently . Even though a pyridine base is used for this approach, elimination towards the norbornene derivative 36 represents only a minor reaction pathway (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we were pleased to find that 2-norbornyl amides undergo oxidative cyclopropanation through amide umpolung chemistry using 2-iodo pyridine, trifluoromethanesulfonic anhydride, and pyridine-N-oxide (PNO) subsequently. [84][85][86][87] Even though a pyridine base is used for this approach, elimination towards the norbornene derivative 36 represents only a minor reaction pathway (Scheme 7). This result showcases the aforementioned tenet of non-classical In conclusion, we have demonstrated that 2-electron oxidative umpolung is a valuable concept for the metal-free construction of cyclopropanes.…”
mentioning
confidence: 99%
“…[2] In doing so, the amide is transformed into an α-trifloxyenamine 2, which resides in a biased equilibrium with the keteniminium salt 3. The latter, a highly electrophilic species, can be intercepted by several nucleophiles, including nucleophilic oxidants, [3][4][5][6][7] and enables a range of unconventional reactivity profiles for the atoms surrounding the original amide functionality. [8][9][10][11][12] The capture of the central electrophilic atom of the keteniminium by modestly nucleophilic entities such as alkenes (in formal [2+2] cycloaddition reactions [13,14] or other ring-forming events) [15] or ethers [16,17] is a well-documented phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to this plethora of methods for α‐functionalisation,[ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] accessing remote positions has remained largely an unexplored area in amide activation. Two examples of γ‐aminoxylation were reported for conjugated acyloxazolidinone (imide) Ti‐enolates by Romea and Urpi (Scheme 1 a ).…”
mentioning
confidence: 99%